Efficient performance evaluations for forward-link cellular DS-CDMA over fading channels - Oh, Ser Wah. (2008)
This research is emphasized on the performance evaluations for forward-link (FL) cellular direct sequence code-division multiple-access (DS-CDMA) systems using some efficient approaches. A generic cellular CDMA which takes into account the effects of path loss, fading, user's spatial distribution and multiple-access interference (MAI) (which also includes inter-cell interference (ICI)) is considered. Three popularly adopted fading statistics, namely Rayleigh, Nakagami and Ricean distributions, are investigated. The performance measure is focused on the average bit-error rate (BER).